COMPREHENSIVE ANALYSIS OF INSULIN RESISTANCE AND SEX HORMONE LEVELS IN WOMEN WITH POLYCYSTIC OVARY SYNDROME: A CASE STUDY FROM AL-SHIRQAT CITY - Wijdan I.A. Abd-alwahab (European Science Publishing, 2024)
The purpose of this study was to determine whether insulin resistance in women with polycystic ovary syndrome (PCOS) is associated with the concentrations of particular sex steroids. A total of 60 women, 20 of them age matched healthy women [control], and 40 women diagnosed with PCOS were included, blood samples were collected from all the women. Sample collection was done from February through March 2024 when all of the participants were 28 to 47 years old. This diagnosis was confirmed on ultrasound examination and clinical examination by specialist physicians in Al Shirqat General Hospital. The results showed a significant increase (P≤0.05) of follicle stimulating hormone (FSH) and luteinizing hormone (LH) and significant decrease (P≤0.05) of inhibin A and estrogen in the PCOS compared with the control group. On the basis of these results, the study concludes that insulin resistance could be a requirement for the development and manifestation of PCOS symptoms.
Keywords: Insulin resistance, diabetes mellitus, inhibin A and polycystic ovary syndrome (PCOS).